Pengaruh Pemberian Pupuk Organik Cair terhadap Pertumbuhan dan Produksi Kentang (Solanum tuberosum L.) - Parman, Sarjana (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2007)
The research about influence of liquid fertilizer on Solanum tuberosum var granola has been done in research garden Getasan, Salatiga,. This research began on May 2001-August 2001. Thr parental Solanum tuberosum seed var granola which able from the farmer from Dieng plateau in Batur regency Banjarnegara district and liquid fertilizer Supra fromSurya Putra Alam Yogyakarta. Complate research design single factor is used, and continued with Duncan Multiple Range Test 5% for data analysis. Result indicated that liquid fertilixer 4 mg/l not influence on hight, fresh and dry weight potatos tuber Solanum tuberosum. Liquid fertilizer by 3 mg/l – 4 mg/l caused fresh weight hight and bulbus diameters. Highly is given withconstrentation liquid fertilizer 4 mg/l caused fresh wight than the other concentration, and not real defferent with the other given treatment with given fertilizer concentration 3 mg/l.